Splenic abscess diagnosed following relapsing sterile peritonitis in a peritoneal dialysis patient: A case report with literature review. Issue 3 (20th February 2021) - Masaki, Chiaki; Matsushita, Kenta; Inoue, Tomoko; Shima, Hisato; Chikakiyo, Motoya; Yamada, Mayumi; Shirono, Ryozo; Tashiro, Manabu; Tada, Hiroaki; Takamatsu, Norimichi; Wariishi, Seiichiro; Okada, Kazuyoshi; et al.
Abstract: Peritoneal dialysis (PD)‐related peritonitis is sometimes complicated with other infections; however, few cases of splenic abscess have been reported. We present the case of a 64‐year‐old PD patient with complicated splenic abscesses diagnosed following relapsing sterile peritonitis. After PD induction, he presented with turbid peritoneal fluid and was diagnosed with PD‐related peritonitis. A plain abdominal computed tomography (CT) did not reveal any intra‐abdominal focus of infection. After empiric intravenous antibiotics, the peritoneal dialysate was initially cleared, with a decrease in dialysate white blood cells (WBC) to 20/µL. However, WBC and C‐reactive protein (CRP) levels remained elevated. A contrast‐enhanced abdominal CT showed two areas of low‐density fluid with no enhancement in a mildly enlarged spleen, making it difficult to distinguish abscesses from cysts. Due to relapsing sterile peritonitis, we performed an abdominal ultrasonography, and suspected splenic abscesses due to rapid increase in size. Repeated imaging tests were useful in establishing a diagnosis of splenic abscesses. Considering the persistent elevation of WBC and CRP levels, imaging findings, and episodes of relapsing peritonitis, we comprehensively formed the diagnosis, and performed a splenectomy as a rescue therapy. We should consider the possibility of other infectious foci with persistent inflammation after resolving PD‐related peritonitis.